Cassava Processing in Enhancing Family Economics in Wailapia Hamlet, Larike Village, West Leihitu District, Central Maluku Regency - Nurdani, Kamalia; Lasaiba, Mohammad Amin; Leuwol, Ferdinand Salomo (JENDELA PENGETAHUAN, 2022)
Cassava is considered the third staple food source after rice and corn. The purpose of this research is to investigate the processing of cassava in improving family economics. This study is descriptive and conducted in one month in Wailapia Hamlet, West Leihitu District, Central Maluku Regency. The sample for this research consists of 20 farmers who specialize in cultivating cassava. The study results show that cassava processing is one of the traditional activities in Wailapia Hamlet, which holds economic value through conventional processing methods. The income of the community members working as cassava farmers is substantial, enabling them to fulfill their daily needs, including clothing, food, shelter, education, and healthcare.